O uso de instrumentos de análise ergonômica no processo de trabalho agrícola: o caso da colheita mecanizada da cana-de-açúcar - Ferreira, Ana Lucy Rodrigues (2014)
The changing in the labor dynamics of the sugarcane harvesting, occasioned by integration of mechanical harvesters, has subjected workers to new working conditions, increasing the interactions with machines, and consequently causing new diseases and work accidents. For improving the performance of work so that this becomes less destructive of human capabilities, is important the use of instruments that allow the identification of risks from man-labor ratio, which are identified through the study of literature in Ergonomics. This study aimed to verify the applicability of the checkpoints of the instrument Ergonomic Checkpoints in Agriculture to the work situation in the context of mechanized harvesting of cane sugar. A review of the relevant issues related to the study was accomplished, considering the themes: Ergonomics, ergonomic analysis tools and working conditions; process of mechanized production of cane sugar, with a focus on the process of harvesting and working conditions; and, finally, the study of the instrument Ergonomic Checkpoints in Agriculture. Subsequently, the analysis of the instrument was accomplished, which was constituted of the following principal stages. Initially, the checkpoints of the instrument were classified considering the workloads, and the similarity of content. Posteriorly, the checkpoints were analysed with respect the applicability in the job functions found in mechanical harvesting of cane sugar process. As a result, 84 checkpoints were classified into 23 clusters and 16 checkpoints were not grouped, among which 11 clusters and 8 checkpoints, which represent 53% of the content of the instrument, were identified with potential of application in the sugarcane mechanical harvesting. The checkpoints identified may assist in the evaluation and implementation of better working conditions, considering the ergonomic point of view, in the mechanical harvesting of sugarcane.